2005
DOI: 10.1002/pssc.200461217
|View full text |Cite
|
Sign up to set email alerts
|

CH x – porous silicon structures for gas sensing applications

Abstract: We have developed a gas sensor for hydrocarbons using layered structures hydrocarbons /porous silicon. Sensitivity of this device, response time and capacitance response to different gases (ethane, ethylene and propane) have been studied. DC and AC electrical measurements were performed to test the sensor and it has been shown that CH x layer-PS/p-Si structure is modified by the gas reactivity on the PS/CHx surface. Finally, FTIR spectroscopy measurements in different gas environments have shown remarkable cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…4). This is slightly different from the results obtained for PSi/CH x and PSi/CH x /Pd structures where the maximum sensitivity was observed at 30 [6] and 10 mV, respectively. [7] In the presence of cigarette smoke, a maximum sensitivity for the PSi/poly(3-hexylthiophene) structure was obtained at 10 mV (a in Fig.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…4). This is slightly different from the results obtained for PSi/CH x and PSi/CH x /Pd structures where the maximum sensitivity was observed at 30 [6] and 10 mV, respectively. [7] In the presence of cigarette smoke, a maximum sensitivity for the PSi/poly(3-hexylthiophene) structure was obtained at 10 mV (a in Fig.…”
Section: Resultscontrasting
confidence: 84%
“…The resulting PSi/CH x structure was successfully used to elaborate a stable platform for the detection of hydrogen and other gases with hydrocarbon CH x layer. [5,6] It was demonstrated that the detection of hydrogen was improved by depositing a thin layer of palladium on the organic coating (CH x ). [7] In the continuation of our work on the use of PSi for gas sensing and to improve the stability and conductivity of the sensor, we propose the covalent grafting of organic conductive species such as conducting polymers onto the PSi surface.…”
Section: Introductionmentioning
confidence: 99%
“…19 The most common stain etchant involves mixtures of HF and HNO 3 of variable concentration 20 ͑or NaNO 2 or NOBF 4 ͒. 21 Substitution of K 2 Cr 2 O 7 , 18,22,23 Na 2 Cr 2 O 7 , 21 KMnO 4 21,24 or KBrO 3 24,25 for the oxidant has also been reported; however, none of these led to particularly good films. The fluoride is usually supplied by HF, although solutions with strong fluorine-containing acids such as HBF 4 and HSbF 6 have also been reported.…”
mentioning
confidence: 99%
“…The development of inexpensive, stable, high-sensitivity Psi-based sensor operating at the room temperature is an important problem (Gabouze et al 2005;He et al 1997;Holzinger et al 1997;Liu and Weppner 1990;Lee et al 1995;Kale et al 1996;Gabouzea et al 2006). The performance of the Psi gas sensor depends upon the morphological properties of surfaces, including pore shape, diameter and uniformity of the porous surface in addition to the thickness of the porous layer (Martinez et al 2008).…”
Section: Introductionmentioning
confidence: 99%